PROTECTION AGAINST TRAFFICKING IN CULTURAL PROPERTY - Cárdenas Oscátegui, Carolina (2010)
Traffic of cultural properties has intensified lately, we see that our patrimony are sold and leave our country, being clandestine excavations, the systematic theft in churches, museums, among others, the most common crimes. From here we try to give a general framework on the existing problems and some approaches for reducing the traffic of cultural property from civil society and especially from the university.